International Society for Companion Animal Infectious Diseases (ISCAID) guidelines for the diagnosis and management of bacterial urinary tract infections in dogs and cats. (May 2019) - Weese, J. Scott; Blondeau, Joseph; Boothe, Dawn; Guardabassi, Luca G.; Gumley, Nigel; Papich, Mark; Jessen, Lisbeth Rem; Lappin, Michael; Rankin, Shelley; Westropp, Jodi L.; Sykes, Jane
Highlights: These guidelines provide recommendations for the diagnosis and management of bacterial urinary tract infections in dogs and cats. Sporadic bacterial cystitis, recurrent bacterial cystitis, pyelonephritis, bacterial prostatitis, and subclinical bacteriuria are addressed. Issues pertaining to urinary catheters, medical dissolution of uroliths and prophylaxis for urological procedures are discussed. Abstract: Urinary tract disease is a common clinical presentation in dogs and cats, and a common reason for antimicrobial prescription. This document is a revision and expansion on the 2011 Antimicrobial Use Guidelines for Treatment of Urinary Tract Disease in Dogs and Cats, providing recommendations for diagnosis and management of sporadic bacterial cystitis, recurrent bacterial cystitis, pyelonephritis, bacterial prostatitis, and subclinical bacteriuria. Issues pertaining to urinary catheters, medical dissolution of uroliths and prophylaxis for urological procedures are also addressed.